Photoionization Instability of Streamer Channel as Possible Reason of Break-Down of Long Air Gaps by Nanosecond Voltage Impulses - V. S. Gladkov; S. I. Levchenko; V. V. Ognivenko; A. V. Pashchenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper shows that while a streamer is moving between electrodes their density and streamer current are increasing as an exponential law due to photoionization effect. This phenomena may be interpreted as a presence of photoionization instability in the channel of moving streamer.Instability increment has been found out. It has been revealed that this instability has threshold character and its origin is initiated by avalanche and streamer transition.